HUBUNGAN PENGETAHUAN, LINGKUNGAN SOSIAL DAN DUKUNGAN KELUARGA IBU HAMIL DENGAN HIPEREMESIS GRAVIDARUM - Sani, Mutiara; Munawaroh, Madinah; Istiana, Istiana (SENTRI: Jurnal Riset Ilmiah, 2023)
Hyperemesis gravidarum is a condition in which patients with nausea and vomiting are more than 10 times in 24 hours, so that their daily work is disrupted and the general condition becomes worse. > 80% of pregnant women in Indonesia experience hyperemesis gravidarum occurs 1-3% of all pregnancies in Indonesia. And pregnant women who experience hyperemesis gravidarum as much as 50-90% are often found in the 1st trimester of pregnancy. Knowledge, social environment and family support are one of the risk factors for hyperemesis gravidarum. This study aims to determine the relationship between knowledge, social environment and family support of pregnant women with Hyperemesis Gravidarum at PMB Bd A Bogor for the period 2021-2022. This research uses descriptive analytic with cross sectional approach. The population of this study amounted to 30 pregnant women with Hyperemesis Gravidarum and the sampling technique used was total sampling with a sample of 30 people. In this study, the instrument used was a questionnaire given to respondents which contained questions or statements using the Guttman scale. The results of this study indicate that there is a significant relationship between knowledge and the incidence of Hyperemesis Gravidarum obtained a P value of 0.001 and the results of OR = 13,938 social environment with the incidence of Hyperemesis Gravidarum obtained a P value of 0.022 and the results of OR = 7.851, and family support with the incidence of anemia obtained a P value Value 0.019 and the result OR = 8.108. Suggestions from this study are for students to add more knowledge, especially regarding Hyperemesis Gravidarum in pregnant women.